Cultural change and the emergence of the knowledge-driven economy - van Wyk, Berte; Jacobs, Anthea HM (South African Journal of Higher Education, 2016)
Duderstadt links transformation at universities to cultural change; extending the link between transformation and cultural change, this paper introduces institutional culture as an important focus for knowledge production. We contend that a change of institutional culture to a more research-oriented culture can be effected by establishing a new knowledge culture which is contingent on the cultural changes that establish the necessary conditions for a research or intellectual culture to develop in the knowledge-driven economy. An analysis of institutional documents of two universities indicates that they think that a change of their institutional cultures is important in the quest for knowledge, and we explore their attempt to attain this objective. Following Naidoo (2008), we contend that the shift from the idea of higher education as a social institution to higher education as an industry may not enhance students’ existing capabilities or induct students into complex intellectual work. This paper argues for an institutional culture that is conducive to the development of a community of scholars in a common pursuit of learning, teaching and research, which may ultimately lead to an increase in the production of new knowledge and a strengthening of the institutional culture or cultural assets rather than producing economic/political assets. Keywords: cultural change, institutional culture, knowledge, knowledge-driven economy, universities, higher education.